Effect of muti-scale thermoelectric magnetic convection on the mushy zone evolution of Al-10 wt%Zn alloy during thermal annealing - Zekun Wang; Sansan Shuai; Chenglin Huang; Yuan Hou; Chaoyue Chen; Tao Hu; Songzhe Xu; Jiang Wang; Zhongming Ren (Journal of Materials Research and Technology)
Effect of a transverse static weak magnetic field (TSMF) on the evolution of the mushy zone of Al–Zn alloys during thermal annealing was investigated through three-dimensional (3D) X-ray tomography, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) analysis. It was demonstrated that the tilting of the solid-liquid interface and the formation of spot defects within the mushy zone under the combined influence of TSMF and temperature gradient zone melting (TGZM). In addition, TSMF can promote the coarsening process of the mushy zone, and with the increase of magnetic field intensity, the length of mushy zone became shorter, and the volume fraction of liquid phase decreased. Numerical simulations were conducted to analyze thermoelectric magnetic convection (TEMC) effects at three scales, including the solid-liquid interface (∼8 mm), inside the liquid droplets (∼80 μm), and the tip of the dendrites (∼350 μm), respectively. The tilting of the solid-liquid interface was attributed to sample-scale TEMC, while the formation of spot defects was linked to solute enrichment due to inter-dendritic TEMC. Furthermore, the coarsening of the mushy zone is attributed to the enhancement of the TGZM effect by the TSMF, which was associated with TEMC inside the droplets in the mushy zone, influencing the dynamics of droplets migration. These findings highlight the potential application of TSMF in influencing the morphology of solid-liquid interface and solute distribution in the mushy zone.